Microplastics alter soil carbon cycling: Effects on carbon storage, CO2 and CH4 emission and microbial community - Sha Chang; Aoyu Zhou; Zhuyao Hua; Han Meng; Fengxiao Zhu; Shiyin Li; Huan He (Cambridge Prisms: Plastics, 2024)
Microplastics (MPs) are carbon-rich polymers that are ubiquitous in the environment. With the increase of plastic production, microplastic pollution may be exacerbated and result in significant changes in microbial communities and biogeochemical processes such as carbon cycling, eventually impacting greenhouse gas emission and carbon storage in terrestrial ecosystems. However, current research on the effect of MPs on soil carbon cycling is still limited, and there is a lack of systematic review of the scattered information obtained from previous studies. Accordingly, this review provides a systematic overview of the current knowledge on the effects of MPs on soil carbon cycling and gives future research suggestions. Emerging evidence indicates that MPs could affect soil carbon stability and CO2 and CH4 emission by modifying soil physicochemical and microbiological properties; though biodegradable MPs often exhibit a greater effect than nonbiodegradable ones, the specific effects are highly dependent on plastic type, size and concentration. The specific mechanisms of MPs’ impact on soil carbon cycles remain elusive, which are discussed mainly from the perspective of microbial changes, including microbial biomass, microbial community composition, and key enzymes and functional genes associated with carbon metabolism. Further research is needed to elucidate whether MPs have a positive priming effect on soil carbon decomposition and the biotic and abiotic mechanisms involved. This review paper helps researchers gain a clearer picture of how and through which way MPs impact carbon cycling in soil ecosystems.